Effect of Cooling Media Viscosities during the Hardening Process on the Mechanical Properties of Steel Materials - Salman Chiad, Jumaa (Journal of Engineering and Sustainable Development, 2012)
Effects of Cooling Media Viscosities during the Hardening process on the Mechanical Properties of Steel Materials. This study involves two parts: the first is manufacturing and testing the steel specimens without heat treatment, while the second is the treatment of the steel specimens by hardening process using different viscosity of quenching cooling oil media. In the beginning, the chemical and mechanical properties of steel specimens are measured and (mid so know the mechanical properties of untreated steel specimens using tensile and hardness and fatigue testing instruments, and the microstructure photo is taken for the same specimen The same tested procedures are followed for all the heat treated steel specimens using four types of cooling oils with different viscosities. The Four types are used with viscosities of(I60,480,960 and 1540) for (S1, S2, S3, and S4 ) respectively. The results show that using cooling oils with different viscosities in the hardening arcs raised (ultimate and yield stresses) with (8.5, 21.0)% '11.1)%,(0.85,13)% and (1.2, I.1)% for (S1, S2, S3, and S4 ), respectively. While young modulus , elongation and reduction in area increased with values of 4, 55,17.3)%, ( 7.7, 70, 30. 7) %, (9.2,100, 36.5)% and (10.2, 100, 34.15)% for S1, S2, S3 and S4, respectively. Brinell hardness also increased with (70.6,56.5,41.17and 23.5)% *S1 S2 ,53 and 54 )respectively. Finally, the endurance stress limit increased aid (62.5,50,3 0, and 5)%for (51 S2, S3, and S4 ), respectively, and the best fatigue life and fatigue limit are recorded with specimen S1...